3‐Level cascaded voltage source converters controller with dispatcher droop feedback for direct current transmission grids. Issue 6 (1st April 2015) - Jamshidifar, Ali Akbar; Jovcic, Dragan
Abstract : The future direct current (DC) grids will require additional control functions on voltage source converters (VSC) in order to ensure stability and integrity of DC grids under wide range of disturbances. This study proposes a 3‐level cascaded control topology for all the VSC and DC/DC converters in DC grids. The inner control level regulates local current which prevents converter overload. The middle control level uses fast proportional integral feedback control of local DC voltage on each terminal which is essential for the grid stability. The hard limits (suggested ±5%) on voltage reference will ensure that DC voltage at all terminals is kept within narrow band under all contingencies. At the highest level, each station follows power reference which is received from the dispatcher. It is proposed to locate voltage droop power reference adjustment at a central dispatcher, to maintain average DC voltage in the grid and to ensure optimal power flow in the grid. This slow control function has minimal impact on stability. Performance of the proposed control is tested on PSCAD/EMTDC model of the CIGRE B4 DC grid test system. A number of severe outages are simulated and both steady‐state variables and transient responses are observed and compared against conventional droop control method. The comparison verifies superior performance of the proposed control topology.